Some questions of the probabilistic description of entropy in the study of molecular physics - Moldabekova, M.S.; Asembayeva, M.K.; Fedorenko, O.V. (Recent Contributions to Physics, 2017)
The explanation problem of the probabilistic description of entropy in the study of the second law of thermodynamics to students is considered. Our discussion is limited by the description of the equilibrium properties that can be calculated as the most probable values. It is emphasized that only irreversible processes contribute to the production of entropy. It is shown that entropy is a random variable whose mean value has a macroscopic physical meaning. Attention is drawn to the fact that the system fluctuates near an average state in the equilibrium condition. It is noted that there is a clear distinction between the macroscopic behavior of the system and the fluctuations. It is shown that the methods of statistical mechanics give not only a description of the average behavior and a method for calculating the fluctuations probability of any magnitude near its mean value. Attention is drawn to the fact that the Boltzmann law of entropy increment is interpreted as a tendency to the disorder increase. This method allows us to determine the most likely macrostate of the system or the most probable distribution of subsystems in the system.